2014
DOI: 10.1155/2014/154769
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Finite-Time Stability and Stabilization of Linear System with Constant Delay

Abstract: Practical systems in engineering fields often require that values of state variables, during the finite-time interval, must not exceed a certain value when the initial values of state are given. This leads us to investigate the finite-time stability and stabilization of a linear system with a constant time-delay. Sufficient conditions to guarantee the finite-time stability and stabilization are derived by using a new form of Lyapunov-Krasovskii functional and a desired state-feedback controller. These conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Solving the optimization problem with ε = 0.5, we can get the minimum value of c 2 in Table . It can be concluded that the method in this paper is less conservative than that in .…”
Section: Numerical Examplesmentioning
confidence: 75%
See 3 more Smart Citations
“…Solving the optimization problem with ε = 0.5, we can get the minimum value of c 2 in Table . It can be concluded that the method in this paper is less conservative than that in .…”
Section: Numerical Examplesmentioning
confidence: 75%
“…Example Considering system with the following parameters : Afalse(tfalse)=[]array1.7array1.7array0array1.3array1array0.7array0.7array1array0.6,-.4emAdfalse(tfalse)=[]array1.5array1.7array0.1array1.3array1array0.3array0.7array1array0.6. …”
Section: Numerical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The controller design problem is solved by using the LMIs and the cone complementarity linearization iterative algorithm. In order to get less conservative criteria, a new form of LKL functional with power weighting function is introduced in [18]. In the last few years, with the great development of the switched system theory, the FTS and FTB problems of switched systems with time delay have received increasing attention (see, e.g., [19,20] and the references therein).…”
Section: Introductionmentioning
confidence: 99%